2019
DOI: 10.1038/s41598-019-49265-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific up-regulation of lncRNAs in peripheral blood of patients with schizophrenia

Abstract: Schizophrenia as a common disabling psychiatric disorder has been associated with dysregulation of several genes and pathways among them are those being regulated by long non-coding RNAs (lncRNAs). Based on the acknowledged roles of lncRNAs in neurodevelopment, in the current study, we assessed expression of six lncRNAs namely HOXA-AS 2, Linc-ROR , MALAT1 , MEG3 , SPRY4-IT1 and UCA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Table S1 summarizes the primers features. We have chosen B2M gene as the reference gene based on our previous observations regrading constant expression of this gene in peripheral blood of patients with schizophrenia 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Table S1 summarizes the primers features. We have chosen B2M gene as the reference gene based on our previous observations regrading constant expression of this gene in peripheral blood of patients with schizophrenia 26 .…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has reported higher expression of both HOXA-AS2 and SPRY4-IT1 in patients with schizophrenia compared with controls. Contradictory to the present study, when authors assessed expression of these genes in gender-based manner, the differences in the expression of these lncRNAs were remarkable only among females (Fallah et al, 2019). These findings suggest different roles of these lncRNAs based on the gender of patients.…”
Section: Discussionmentioning
confidence: 74%
“…In the first example, we identify MALAT1 (Metastasis Associated Lung Adenocarcinoma Transcript 1) as an NDD-related enhancer-ncRNA, located within chromosome 11 with 12.7kb in length; this lncRNA is highly expressed in neurons [32]. It has been shown that the loss of the MALAT1 negatively affects the expression of neighboring genes, including genes which are significantly decreased in expression within several brain regions relevant to schizophrenia [33]. Furthermore, a study reported that MALAT1 expression was significantly different in patients with schizophrenia compared with healthy subjects [34], and MALAT1 is also implicated in ASD [35].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the loss of the MALAT1 negatively affects the expression of neighboring genes, including genes which are significantly decreased in expression within several brain regions relevant to schizophrenia [33]. Furthermore, a study reported that MALAT1 expression was significantly different in patients with schizophrenia compared with healthy subjects [34], and MALAT1 is also implicated in ASD [35].…”
Section: Association Of Enhancer Ncrnas With Decipher Phenotypesmentioning
confidence: 99%